Flexibility of Freight Transport Sectors: An Exploration of Carriers’ Responses to External Pressure on Prices and Service - Runhaar, Hens; van der Heijden, Rob; Kuipers, Bart (European Journal of Transport and Infrastructure Research, 2002)
In this paper, we explore how government policies in the field of transport may affect future freight rates, transit times, and delivery reliability. In particular, attention is paid to the ‘absorptive capacity’ of freight carriers, i.e. the extent to which they can reduce the effects of such policies by adapting their operations. Two policy scenarios are examined: one in which marginal social cost pricing becomes policy in the European Union, and one in which investment in infrastructure networks is insufficient to accommodate the future increase in traffic demand, inducing a strong increase in congestion. Six modes of transportation are included in the analysis, namely road haulage, rail transport, inland navigation, short sea shipping, airfreight, and deep sea container shipping. The study relied on experts’ opinions and estimations, which were collected by means of a Delphi survey. The expectation is that notably road transport will face difficulties in coping with the two scenarios. Its absorptive capacity proves to be the lowest, which deteriorates its competitive position vis-à-vis other modes. Yet, a weakened competitive position of road haulage is also expected autonomously.